STATE FINANCIAL SUPPORT FOR SMALL BUSINESS DURING THE CORONAVIRUS CRISIS IN EUROPEAN COUNTRIES - V. Humeniuk; Iu. Umantsiv; A. Dligach; N. Ivanova; H. Umantsiv (Фінансово-кредитна діяльність: проблеми теорії та практики, 2021)
Abstract. The aim of the conducted research is elaboration of conceptual statements and formulation of practical recommendations aimed at development of the methodological bases of state financial support for small business. On the basis of the existing theoretical statements, discovery of essential characteristics, peculiarities and systematisation of the obtained results of the research, conceptual approaches to interpretation of the features of state financial support for small business during the coronavirus crisis have been suggested. Small business is an important component of the economic system of any country. It ensures formation of the complex structure of the market for goods and services, development of efficient competition and promotes addressing the needs of consumers in conditions of formation of their sovereignty. State financial support for small business in European countries is at different stages of development. In the EU countries, financial policy of small business regulation is an example of state intervention in the mechanism of market self-regulation in order to solve social and economic problems by changing the economic behaviorur of small enterprises. The formational process, strategic priorities of state financial support for small business in European countries and macroeconomic instruments for its implementation during the coronavirus crisis have been studied. Changes in the concern of the world community in forms of state financial support for small business have been detected. A comparative and analytical examination of the instruments for macroeconomic financial regulation, which are being used during the COVID-19 pandemic in Europe, has been conducted. The research shows the importance of small business in terms of solving economic and social problems of social development, outlines the situation of state financial support in the EU countries in comparison with Ukrainian small enterprises, determines the general features and differences in state regulation of entrepreneurship. The practical significance of the obtained results consists in the fact that the main scientific statements of the article can be used in practice of state and regional management of small business.